2022
DOI: 10.2147/ccide.s379171
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Oral Health Knowledge and Practices Among Adults in Jeddah, Saudi Arabia

Abstract: Aim To determine the knowledge and practices of adults regarding oral health and to determine the associated gender differences. Methods A cross-sectional study design was used in Jeddah, Saudi Arabia, and a total of 1330 adults participated. Data were collected using self-administered validated questionnaire to gather information about sociodemographic data, oral health knowledge and practices. The scores of the oral health knowledge were calculated. Linear and logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 35 publications
8
12
0
4
Order By: Relevance
“…Our study found that women are 4% more likely to visit OHC providers compared to men, consistent with previous research ( Rajeh, 2022 ). These results call for a profound examination of the factors that foster frequent dental visits among women and inhibit such visits among men.…”
Section: Discussionsupporting
confidence: 93%
“…Our study found that women are 4% more likely to visit OHC providers compared to men, consistent with previous research ( Rajeh, 2022 ). These results call for a profound examination of the factors that foster frequent dental visits among women and inhibit such visits among men.…”
Section: Discussionsupporting
confidence: 93%
“…The study had several important findings. Individual and familial factors were significantly associated with the use of most oral hygiene methods: males had significantly lower odds than females of using toothbrushes, in agreement with the literature [ 19 , 31 ] which may be because females place greater importance on their oral health than males [ 32 ]. The exception to this association was that males had higher odds of using miswak which needs to be explored in future studies.…”
Section: Discussionsupporting
confidence: 88%
“…Currently, evidence from this paper has con rmed that the association of oral health knowledge with frailty had statistical discrepancies concerning educational attainments. Our study revealed that the connection between oral health knowledge and frailty was signi cant only in older people with primary school or lower education, which corresponds to the conclusions of a previous study [49]. Also, this may because older people with lower education levels do not fully understand or receive appropriate oral hygiene maintenance training, they may not be aware of the importance of regular dental examinations [50,51].…”
Section: Discussionsupporting
confidence: 83%